2021
DOI: 10.1111/jfpp.15422
|View full text |Cite
|
Sign up to set email alerts
|

Stability of iron and vitamin A in pasta enriched with variable plant sources during processing and storage

Abstract: Globally, more than 2 billion people suffer from one or more micronutrient affliction (Bailey et al., 2015). Lack of nutritional knowledge and consumption of unbalanced or processed diets are some of the contributors for the same. Particularly in developing nations, there is co-existence of multiple micronutrient deficiencies also known as "hidden hunger". Prolonged existence of these deficiencies can lead to impaired physical and defected cognitive growth, which ultimately affects the nation's development. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…This was attributed to the high fiber and protein content of WGP. Fiber helps in high absorption of water into pasta (Kaur et al, 2012; Sharma et al, 2021) thus increases WAC and volume expansion. Studies by Surasani et al (2019) and Gupta et al (2021) concluded that pasta containing a good amount of protein expands more during cooking and thus increases the volume.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was attributed to the high fiber and protein content of WGP. Fiber helps in high absorption of water into pasta (Kaur et al, 2012; Sharma et al, 2021) thus increases WAC and volume expansion. Studies by Surasani et al (2019) and Gupta et al (2021) concluded that pasta containing a good amount of protein expands more during cooking and thus increases the volume.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the paradigm shift in the lifestyle of the consumer because of globalization and urbanization, there is an increasing demand for health-based and convenient products (Bobade et al, 2021). The WHO and FDA recommend pasta as a good carrier for bioactive compounds and micro-nutrient delivery (Sharma et al, 2021). Pasta is one of the popular food products owing to its ease of preparation, low cost, storage stability, and nutrition qualities.…”
mentioning
confidence: 99%
“…Duszkiewicz-Reinhard et al [10] did not observe any change in the color, mouthfeel, external appearance, and general acceptability during storage for 6 months at 23 • C. Additionally, Verardo et al [11] related a shelf life comparable to control pasta in functional spaghetti. In contrast, Sharma et al [32] observed a decline in the overall acceptability scores of supplemented pastas with time, accentuated after the third month. The same authors related that a higher temperature (40 vs. 25 • C) and the type of packaging influenced the sensory properties of stored pasta.…”
Section: Sensory Analysismentioning
confidence: 84%
“…The presence of these non‐starch polysaccharides has higher capacity for hydration, therefore restricting the plasticizer and therefore inhibiting an increase in the pasting viscosities. A reduction in the final viscosity indicates that uniform starch granules had higher capacity to crystallise during the process of retrogradation (Sharma et al ., 2021). Decrease in the breakdown viscosity on bran incorporation could be ascribed to the decrease in the rate of swelling of the starch granule and absorption of water by the fibre present in the bran.…”
Section: Resultsmentioning
confidence: 99%
“…Pancreatic α‐amylases extraction was carried out for in vitro starch digestibility, while pepsin and pancreatin digestions were undertaken for in vitro protein digestibility according to the methods described by Sharma et al . (2021) detailed in File S1.…”
Section: Methodsmentioning
confidence: 99%